Billy Wilder as a Critic of Humanitarian Intervention - Gavriilidis, Akis; Edwards, Paul (Identities: Journal for Politics, Gender and Culture, 2019)
What follows is a chapter from a book originally published by the author in Greek, under the title Μπίλι Ουάιλντερ. Η (αυτο)κριτική του χολιγουντιανού θεάματος [Billy Wilder: The (Self-)Criticism of the Hollywood Spectacle] (Athens: Aigokeros, 2009). The book was translated into English but was never published. The version published here contains some inevitable additions and adaptations. Author(s): Akis Gavriilidis Title (English): Billy Wilder as a Critic of Humanitarian Intervention Translated by (Greek to English): Paul Edwards Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 22-30 Page Count: 9 Citation (English): Akis Gavriilidis, “Billy Wilder as a Critic of Humanitarian Intervention,” translated by Paul Edwards, Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019): 22-30.